Wychowanie w rodzinie włościańskiej w świetle listów czytelników „Zorzy” - Krakowiak, Małgorzata (Wydawnictwo Naukowe EDUsfera. Ewa Jurczyk-Romanowska, 2021)
The aim of the article was to indicate and discuss upbringing in peasant families, which was described in readers’ letters published in the periodical „Zorza” and its continuations from 1905 until 1918. In the present article, the author tried to answer the following questions: How was the educational influence in the family assessed in the letters and wha tpostulates were formulated? How was the implementation of care and educational tasks in the families described in the letters published in the peasants’ press? What threats tothe family, and its stability, and what educational role, were indicated in the readers’ correspondence?
Keywords: family upbringing; peasant family; „Zorza” - periodical; socio-cultural press